Legal status and refugees' perceptions of institutional justice: The role of communication quality - Emily Frank; Anton Nivorozhkin (Public Administration Review, 2024)
What factors influence refugees' perceptions of justice in bureaucratic institutions? As global migration movements draw increasing attention, migrants' experiences as constituents in destination countries merit further research. Drawing evidence from the 2018 survey of refugees participating in the German Socio-Economic Panel, this article examines the role of legal status in shaping perceptions of justice at government offices. Our findings highlight a stark contrast: refugees with unstable legal statuses often perceive bureaucratic proceedings as less just compared to those with firmer legal standings. However, refugees' perceptions of a more positive encounter their encounters with street-level bureaucrats can act as a buffer against the negative effects of legal status on perceptions of justice at government offices. These insights underscore a pressing policy implication: asylum procedures, currently marked by ambiguity and delays, could benefit significantly from enhanced communication quality on the part of street-level bureaucrats.
Keywords: 320; Kommunikation; Flüchtling; SOEP; Bundesrepublik Deutschland; Gerechtigkeit; Justiz; Asylbewerber; öffentliche Verwaltung